Factors associated with fatal cases of acute respiratory infection (ARI) among hospitalized patients in Guatemala - Sara Tomczyk; John P. McCracken; Carmen Lucia Contreras; Maria Renee Lopez; Chris Bernart; Juan Carlos Moir; Kenneth Escobar; Lisette Reyes; Wences Arvelo; Kim Lindblade; Leonard Peruski; Joe P. Bryan; et al. (BMC, 2019)
Abstract Background Acute respiratory infection (ARI) is an important cause of mortality in children and adults. However, studies assessing risk factors for ARI-related deaths in low- and middle-income settings are limited. We describe ARI-related death and associated factors among children aged < 2 years and adults aged ≥18 years hospitalized with ARI in Guatemala. Methods We used respiratory illness surveillance data in Guatemala from 2007 to 2013. ARI was defined as evidence of acute infection and ≥ 1 sign/symptom of respiratory disease in hospitalized patients. Clinical, sociodemographic, and follow-up data were gathered. Nasopharyngeal/oropharyngeal swabs were collected from patients with ARI and tested for 6 respiratory viruses; urine was collected only from adults with ARI and tested for pneumococcal antigen. Blood cultures and chest radiographs were performed at the physician's discretion. Radiographs were interpreted per World Health Organization guidelines to classify endpoint pneumonia (i.e. suggestive of bacterial pneumonia). Multivariable logistic regression was used to compare characteristics of patients with fatal cases, including those who died in-hospital or were discharged in a moribund state, with those of patients with non-fatal cases. Results Among 4109 ARI cases identified in hospitalized children < 2 years old, 174 (4%) were fatal. Median age at admission was 4 and 6 months for children with fatal and non-fatal cases, respectively. Factors associated with fatality included low weight-for-age, low family income, heart disease, and endpoint pneumonia; breastfeeding and respiratory syncytial virus (RSV) detection were negatively associated with fatality. Among 1517 ARI cases identified in hospitalized adults ≥18 years, 181 (12%) episodes were fatal. Median age at admission was 57 years for adults with fatal and non-fatal cases. Low body mass index, male sex, kidney disease, and endpoint pneumonia were significantly more common among patients with fatal versus non-fatal cases. Conclusions Our findings highlight some of the factors that must be addressed in order to reduce ARI-related mortality, including promotion of good nutrition, breastfeeding, management and prevention of chronic comorbidities, and poverty reduction. Although no specific pathogen increased risk for death, endpoint pneumonia was significantly associated with fatality, suggesting that the pneumococcal conjugate vaccine could contribute to future reductions in ARI-related mortality.